2016
DOI: 10.5194/hess-20-3601-2016
|View full text |Cite
|
Sign up to set email alerts
|

Bias correcting precipitation forecasts to improve the skill of seasonal streamflow forecasts

Abstract: Abstract. Meteorological centres make sustained efforts to provide seasonal forecasts that are increasingly skilful, which has the potential to benefit streamflow forecasting. Seasonal streamflow forecasts can help to take anticipatory measures for a range of applications, such as water supply or hydropower reservoir operation and drought risk management. This study assesses the skill of seasonal precipitation and streamflow forecasts in France to provide insights into the way bias correcting precipitation for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
167
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(204 citation statements)
references
References 58 publications
(64 reference statements)
8
167
1
3
Order By: Relevance
“…GCM-based forecasts are, however, sharper than ESP forecasts, which combined with the high biases lead to a poorer accuracy than ESP forecasts. Our results are directly comparable to those of Crochemore et al, (2016) as they also deal with seasonal streamflow forecasting 10 with ECMWF System 4 for a region located not too far from our study area. They also found GCM-based forecast to be sharper than those of the ESP.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…GCM-based forecasts are, however, sharper than ESP forecasts, which combined with the high biases lead to a poorer accuracy than ESP forecasts. Our results are directly comparable to those of Crochemore et al, (2016) as they also deal with seasonal streamflow forecasting 10 with ECMWF System 4 for a region located not too far from our study area. They also found GCM-based forecast to be sharper than those of the ESP.…”
supporting
confidence: 75%
“…This rather mild enhancement was also found by Crochemore et al, (2016). Moreover, postprocessing alone does a better job in removing biases in the mean, that in turn help to ameliorate issues with the statistical consistency.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Only forecasts with lead times up to 90-days were considered. In a previous study, several bias corrections were applied to System 4 precipitation forecasts and compared based on their impacts on seasonal streamflow forecasts (Crochemore et al, 2016). The study showed that the empirical distribution mapping of daily values improved the reliability of both precipitation and streamflow forecasts.…”
Section: Observed and Forecast Hydrometeorological Datamentioning
confidence: 99%
“…2) aims at post-processing the forecast products. Depending on the characteristic of the forecast, we perform bias correction by means of the change factor approach (Crochemore et al, 2016) or the quantile mapping technique (Déqué, 2007). Given the strong intra-annual seasonal cycle of our study site, the bias correction was applied on a monthly basis.…”
Section: Post-processing Of Forecast Productsmentioning
confidence: 99%